2018
DOI: 10.3390/ijgi7090379
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction and Selection of Sentinel-1 Dual-Pol Data for Global-Scale Local Climate Zone Classification

Abstract: The concept of the local climate zone (LCZ) has been recently proposed as a generic land-cover/land-use classification scheme. It divides urban regions into 17 categories based on compositions of man-made structures and natural landscapes. Although it was originally designed for temperature study, the morphological structure concealed in LCZs also reflects economic status and population distribution. To this end, global LCZ classification is of great value for worldwide studies on economy and population. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Second, due to the fact that less then 10% of the participants lived in Berlin or were familiar with the city, it was not possible to investigate the influence of local knowledge on the classification results. Even though, currently research is done investigating the potential of continental-scale LCZ maps [26][27][28], the question on local knowledge remains important. In this respect, it might be better to include more cities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to the fact that less then 10% of the participants lived in Berlin or were familiar with the city, it was not possible to investigate the influence of local knowledge on the classification results. Even though, currently research is done investigating the potential of continental-scale LCZ maps [26][27][28], the question on local knowledge remains important. In this respect, it might be better to include more cities.…”
Section: Discussionmentioning
confidence: 99%
“…Qui et al (2018) [35,36] particularly focused on data/feature choice including optical data such as Landsat-8 and Sentinel-2, as well as additional datasets such as the Global Urban Footprint (GUF), the OpenStreetMap (OSM) layers buildings and land use, and the Visible Infrared Imager Radiometer Suite (VIIRS)-based Nighttime Light (NTL). [37,38], on the other hand, explored the potential of Sentinel-1 polarimetric SAR data for LCZ classification. Despite the rapid advancements in spatio-temporal LCZ mapping, to date, the large number of LCZ maps created for cities and regions around the world (see, e.g., references in [28,33,35,[39][40][41]) are typically static in time.…”
Section: Introductionmentioning
confidence: 99%
“…The categories related to this study are mostly man-made structures, except for the category of vegetation. It has been demonstrated that VH-polarized data contributes the most to the classification of man-made structures [67]. The second viewpoint is to explain the phenomenon from the perspective of visual appearance.…”
Section: Overall Performance Of Opensarurban For Urban Target Catementioning
confidence: 99%